The combination of hydrogen/deuterium exchange or chemical cross-linking techniques with mass spectrometry: mapping of human 14-3-3ζ homodimer interface - Haladová, Kateřina; Mrázek, Hynek; Ječmen, Tomáš; Halada, Petr; Man, Petr; Novák, Petr; Chmelík, Josef; Obšil, Tomáš; Šulc, Miroslav (Journal of structural biology, 2012)
Hydrogen/deuterium (H/D) exchange or chemical cross-linking by soluble carbodiimide (EDC) was employed in combination with high-resolution mass spectrometry (MS) to extend our knowledge about contact surface regions involved in the well-characterized model of interaction between two molecules of human 14-3-3ζ regulatory protein. The H/D exchange experiment provided low resolution mapping of interaction in the homodimeric 14-3-3ζ complex. A lower level of deuteration, suggesting structural protection, of two sequential segments has been demonstrated for dimeric 14-3-3ζ wild type relative to the monomeric mutant 14-3-3ζ S58D. The N-terminal sequence (the first 27 residues) from one subunit interacts with region αC'and αD'-helices (residues 45-98) of the other molecule across the dimer interface. To identify interacting amino acid residues within the studied complex, a chemical cross-linking reaction was carried out to produce the covalent homodimer, which was detected by SDS-PAGE. The MS analysis (following tryptic in-gel digestion) employing both high resolution and tandem mass spectrometry revealed cross-linked amino acid residues. Two alternative salt bridges between Glu81 and either Lys9 or the N-terminal amino group have been found to participate in transient interactions of the 14-3-3ζ isotype homodimerization. The data obtained, which have never previously been reported, were used to modify the published 14-3-3 crystal structure using molecular modeling. Based on our findings, utilization of this combination of experimental approaches, which preserve protein native structures, is suitable for mapping the contact between two proteins and also allows for the description of transient interactions or of regions with flexible structure in the studied protein complexes.
Keywords: Molecular Dynamics Simulation; simulace molekulární dynamiky; multimerizace proteinu; Deuterium Exchange Measurement; Recombinant Proteins; Amino Acid Sequence; 14-3-3 Proteins; Mutation; molekulární sekvence - údaje; konformace proteinů; Cross-Linking Reagents; Humans; hmotnostní spektrometrie; Mass Spectrometry; Molecular Sequence Data; sekvence aminokyselin; Protein Multimerization; karbodiimidy; rekombinantní proteiny; Carbodiimides; vodík-deuteriová výměna; mapování interakce mezi proteiny; Protein Interaction Mapping; mutace; lidé; proteiny 14-3-3; Protein Conformation; reagencia zkříženě vázaná